Introducing More Practice in The Educational System of Students Studying in The Field of Construction - A. M. Makhmudov; U. Q. Toshmatov (Web of Journals Publishing, 2023)
Construction is a field that requires a combination of theoretical knowledge and practical skills. However, the educational system for students studying construction often emphasizes theoretical knowledge at the expense of practical experience. In this article, we will discuss the importance of introducing more practice into the educational system of students studying in the field of construction.
Keywords: education, practical experience, problem-solving skills, construction industry.